Dampak Globalisasi Terhadap Risiko Keuangan Perusahaan: Risiko Nilai Tukar, Suku Bunga, dan Risiko Negara - Moch. Iqbal Zulfikar Pd; Loso Judijanto (CEMERLANG : Jurnal Manajemen dan Ekonomi Bisnis, 2024)
This study aims to analyze the impact of globalization on corporate financial risk, focusing on exchange rate risk, interest rate risk, and country risk. The research employs a quantitative method, utilizing data from the annual financial reports of multinational companies listed on stock exchanges from 2010 to 2020. Data analysis is conducted using descriptive and inferential statistical techniques, including multiple regression to evaluate the relationship between independent variables (globalization factors such as exports, imports, and foreign direct investment) and dependent variables (levels of financial risk faced by companies). The findings indicate that globalization significantly influences these three types of financial risk. Companies involved in international trade tend to face greater exchange rate fluctuations, dynamic interest rate changes, and higher country risk compared to companies operating in domestic markets. To manage these risks, companies need to develop comprehensive risk management strategies, including the use of derivative instruments, thorough political and economic risk analysis, and investment in advanced technologies. Continuous training and fostering a strong risk culture within the organization are also critical factors in effective risk management. This study provides in-depth insights into how globalization affects corporate financial risk and offers strategic recommendations to enhance financial resilience in a global context.